Utilizando a modelagem matemática para auxiliar o ensino-aprendizagem do conteúdo de funções - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
This research aims to investigate the relevance that some students of the first year of high school give to the content of functions through an inverted perspective of teaching-learning of the subject, in which the student is seen as the agent constructing the knowledge itself. To elaborate this work, we have revisited educational legislation such as LDB, BNCC and the PCN + of the mathematics discipline and, as methodology, we use principles of mathematical modeling as a key for students to construct and give opinions in the elaboration of models that mathematically solve everyday situations and of Sciences. Besides, the research developed with the theoretical foundation of meaningful learning from the perspective of Moreira and the semiotic representations presented by Raymond Duval was also associated. The problem situations were elaborated a priori by the researcher, followed by orientations during a month, with weekly meetings, and the visions of these were verified through semistructured questionnaires applied for data collection, which were later compiled. The results were satisfactory and confirm/refute similar research.
Using the mathematical model to teaching-learning of the content of functions
Keywords: Matemática - Estudo e ensino (Ensino médio); Funções (Matemática); Modelos matemáticos; CIÊNCIAS EXATAS E DA TERRA: MATEMÁTICA; Aprendizagem significativa; Semiótica; Modelagem matemática